2019
DOI: 10.1016/j.eats.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Superior Capsular Reconstruction With Arthroscopic Rotator Cuff Repair in a “Functional Biologic Augmentation” Technique to Treat Massive Atrophic Rotator Cuff Tears

Abstract: Surgical treatment of patients with massive rotator cuff tears is unpredictable because of a low healing rate and high incidence of clinical failure. Arthroscopic superior capsular reconstruction has emerged as a promising technique in treating younger, active patients with massive irreparable rotator cuff tears. Superior capsular insufficiency has been theorized to be a factor in the higher failure rate for repairs of massive tears, and there have been proposals of superior capsular repair in addition to rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The technique has been referred to as "functional biologic augmentation" or "over-the-top repair". This procedure has been described as having the goal of decreasing the AHI to allow the rotator cuff to be stretched to reach the native attachment site 14,15 . However, we noticed the phenomenon that, in some cases, after the release technique and even SCR was performed, the remnant cuff tissue could not be reapproximated to its native footprint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique has been referred to as "functional biologic augmentation" or "over-the-top repair". This procedure has been described as having the goal of decreasing the AHI to allow the rotator cuff to be stretched to reach the native attachment site 14,15 . However, we noticed the phenomenon that, in some cases, after the release technique and even SCR was performed, the remnant cuff tissue could not be reapproximated to its native footprint.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in some cases, the humeral head migrated superiorly again because of the "creep" (graft get stretched) phenomenon, which results in increased joint laxity, and may lead to SCR failure 13 . Although the importance of restoring the remnant rotator cuff tissue to maximize clinical outcomes when performing SCR has been highlighted 14,15 , problems such as extreme tension at the suture site, high re-tear rates, and incomplete dynamic function recovery after SCR still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue mobility, quality, and tension are important considerations when determining the ideal method of surgical repair of full-thickness rotator cuff tears. If the rotator cuff tendon is unable to mobilize to the footprint or if there is excessive tension on the mobilizable tendon, procedures like the SCR or SCR combined with cuff repair 1 , 2 , 3 , 4 , 5 should be favored over primary repair. For the repairable tear, poor tissue quality necessitates graft augmentation to provide additional thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic SCR using a dermal allograft has also shown favourable short-to-mid-term improvements in subjective and functional outcomes ( 2 , 8 , 13 , 14 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ). Hirahara et al reported that SCR with dermal allograft resulted in better functional outcomes, American Shoulder and Elbow Surgeons (ASES) scores (49–85), and decreased visual analogue scale (VAS) scores (5.3–0.9; P < 0.001) in 18 patients.…”
Section: Technical Considerationsmentioning
confidence: 99%